BIOECOLOGY OF DIORYCTRIA ABIETELLA DENIS AND SCHIFF. A PEST OF CONIFERS IN THE NORTH-WESTERN HIMALAYA - T.D VERMA (BIOTROPIA, 1994)
Cones and seeds of conifers, such as Pinus roxburghii, P. wallichiana, P. gerardiana, Cedrus deodara, Abies pindrow and Picea smithiana are seriously damaged by Dioryctria abietella Denis and Schiff. (Lepidoptera : Pyralidae) in the North-Western Himalayan region of India. Bioecological studies carried out during 1991 - '92 revealed that the females laid whitish, elliptical eggs singly on the depressed surface of the young cones. The average egg size was 1.00 ± 0.11 x 0.60 ±0.08 mm and this stage lasted for 3 - 5 days. The larval stage passed through five instars. All the instars differed in appearance, size and duration and larvae became full-fed in an average of 24.8 ± 1.9 days. The full-fed larva spun a cocoon around itself, sealed it with white papery membrane and pupated inside the cone or any other outside protected place. The prepupal and pupal periods lasted for 7-8 and 10-14 days, respectively. The pupa was dark brown, 13.8 ± 0.07 mm in length. Total period from egg to adult varied from 46 to 59 days (52.7 ±4.8 days). Adults were dirty brown in appearance and were 13.59±0.115 mm long with an average wing expanse of 29.0 ± 1.00 mm. They lived for 4 to 5 days. Under laboratory conditions, the pest completed two generations per year and full-fed larvae of 3rd generation overwintered during September - October. Two larval parasites belonging to order Hymenoptera and Diptera, and a fungal pathogen (Fusarium sp.) were found associated with this pest. The detailed biology, nature and extent of damage, along with its distribution have been discussed and methods of control suggested. Key Words: Insect biology, Insect ecology, Dioryctria abietella, Coniferae, North-Western Himalaya, Forest pests